MATERIALS AND RESOURCES FOR TEACHING ITALIAN PRAGMATICS (ItalianoLinguadue, 2022)
This study aims to describe the materials and the resources utilized for teaching Italian pragmatics, both in foreign and second language contexts. 139 teachers of Italian answered an online questionnaire which elicited information about the materials and resources they used in the classroom as well as information regarding their teaching techniques. Their answers were clustered into five main categories. The results revealed that the most commonly used materials were printed, audiovisual, self-produced, students’ oral production and digital materials. Within these categories, textbooks (printed materials) and videos (audiovisual material) were considered as the most preferred materials by the teachers. Regarding teaching techniques, the most frequently used by teachers were role plays, watching videos and listening exercises. The findings of the present study suggest that textbooks, the main resource for teaching pragmatics, should be implemented with specific activities on this topic. By receiving guidelines, teachers could appropriately teach pragmatics in their classes without the need to create their own materials. Materiali e risorse per l’insegnamento della pragmatica italianaQuesto studio mira a descrivere i materiali e le risorse utilizzate per l’insegnamento della pragmatica italiana, sia in contesti di lingua straniera che di lingua seconda. 139 insegnanti di italiano hanno risposto a un questionario online predisposto allo scopo di raccogliere informazioni sui materiali e le risorse che usavano in classe e sulle loro tecniche di insegnamento. Le risposte degli insegnanti sono state raggruppate in cinque principali categorie. I risultati hanno rivelato che i materiali più comunemente usati sono a stampa, audiovisivi, autoprodotti, produzione orale degli studenti e digitali. All’interno di queste categorie, i libri di testo (materiali stampati) e i video (materiale audiovisivo) sono i materiali preferiti dagli insegnanti. Per quanto riguarda le tecniche di insegnamento, le più utilizzate dagli insegnanti risultano essere i giochi di ruolo, la visione di video e gli esercizi di ascolto. I risultati del presente studio suggeriscono che i libri di testo, la risorsa principale per l’insegnamento della pragmatica, dovrebbero essere implementati con attività specifiche a questo dedicate. Disponendo di linee guida, gli insegnanti potrebbero insegnare in modo appropriato la pragmatica nelle loro classi senza avere la necessità di creare materiali propri.